1998
DOI: 10.1038/bjc.1998.632
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutation, but not p53 overexpression, correlates with survival in head and neck squamous cell carcinoma

Abstract: Summary Survival in squamous cell carcinoma of the head and neck (HNSCC) was compared with overexpression and mutation of the p53 gene. Archival tissue from 77 tumours was analysed for protein expression using immunohistochemistry (IHC) with the monoclonal antibody Do-7, and for the presence of mutation in exons 5-8 using single-stranded conformation polymorphism (SSCP), followed (4/19) or low protein expression (4/33). Fifty-eight patients were eligible for survival analysis. There was a strong correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
2
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 32 publications
2
65
2
5
Order By: Relevance
“…53 Therefore, mutational analysis of p53 by direct sequencing is more likely to be accurate and reliable than immunohistologic methods. 20,48,54 However, the analysis is problematic in that normal cells without mutations may present around tumor cells with p53 mutation in the samples, resulting in a lower detection of mutation genes. The laser capture microdissection system employed in the current study could solve the problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…53 Therefore, mutational analysis of p53 by direct sequencing is more likely to be accurate and reliable than immunohistologic methods. 20,48,54 However, the analysis is problematic in that normal cells without mutations may present around tumor cells with p53 mutation in the samples, resulting in a lower detection of mutation genes. The laser capture microdissection system employed in the current study could solve the problem.…”
Section: Discussionmentioning
confidence: 99%
“…In advanced laryngeal carcinoma, Bradford et al 58 reported that p53 mutation is associated with a poor prognosis. In head and neck SCC besides maxillary sinus SCC, Mineta et al 20 showed p53 mutation to be an independent risk factor for disease specific death. In the current study, the univariate analysis and the KaplanMeier method showed that p53 mutation was closely associated with poor disease-free survival in maxillary sinus SCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data, however, confirmed the results of previous studies that failed to establish an association of p53 expression with survival in head and neck cancers. 31,32 The absence of an impact of p53 expression on tumor progression might possibly be explained by recent studies that report the predictive value of p53 mutation 33 and mutation within DNA-binding surface region of p53 34 for shortened survival rather than p53 protein expression in head and neck cancers. More comprehensive studies combined with mutational analysis are required for determining the outcomes of cancer patients using immunohistochemistry.…”
Section: Molecular Marker Expression In Oral Cancer M Shiraki Et Almentioning
confidence: 99%
“…Tumor cells with mutations in the P53 gene generally result in accumulation and overexpression of the P53 protein (Iggo et al, 1990;Lane, 1992;Wilson et al, 1995;Koch et al, 1996;Silvestrini, 1996;Dumaz et al, 1997;Mineta et al, 1998;Gallo et al, 1999;Saunders et al, 1999;Taylor et al, 1999;Obata et al, 2000;Agarwal et al, 2001). However, there is often discordance between the mutation status of the P53 gene and the evaluation of the protein levels (i.e., expression of the protein does not always correlate with underlying mutations, and underlying P53 mutations may not always result in overexpression of the protein).…”
Section: P53mentioning
confidence: 99%